MODERN SCIENTIFIC TENDENCIES IN NUTRICIOLOGY AND ITS INFLUENCE ON THE DEVELOPMENT OF CHILDREN'S FOOD MARKET - O.A. Matalygina ("Paediatrician" Publishers LLC, 2010)
The article is devoted to the influence of some modern scientific discoveries in nutriciology on the formation of market of industrially manufactured children's food.Key words: children, nutrition.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(2):82-89)